Driven Towards Death – A Psychoanalysis Approach In Interpreting The Novel Kokoro By Natsumi Soseki - Jordan Marelino Parsaulian Naibaho; Mike Wijaya Saragih (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This paper aims to attest the author's interpretation that Sensei's character in the novel "Kokoro" by Natsume Soseki, fits into the category of individuals who are driven to death. Through Sigmund Freud's psychoanalytic approach, the writer is expected to prove his interpretation through an integrated analysis. Psychoanalytic elements contained in the novel include instincts, structure of personality and death drive. According to Freud, human instincts are divided into two: life instincts and death instincts. In Freud’s structure of personality, the discussed topic will be focused on the id, ego, and superego. Id, ego, and superego will be the subject of how Sensei's character falls into the category of individuals who are driven to death. The method used in answering the research problems is by using close reading, focalization, and data collection. The novel "Kokoro" tells the characters of I and Sensei. I and Sensei are two people met just by chance, unrelated to each other. This paper focuses on Sensei’s part where he tells his past to I. At the end of the contents of the letter, Sensei stated that he had committed suicide. The letter turns out to be Sensei’s testament. The results of this paper are, in the novel "Kokoro", Sensei's character is an individual who: 1) has a life instinct and a death instinct in different periods of time, 2) has an id, ego, and superego which is proof that Sensei has the trait of being driven to death.